Four-Dimensional Microvascular Analysis Reveals That Regenerative Angiogenesis in Ischemic Muscle Produces a Flawed Microcirculation. Issue 9 (28th April 2017) - Arpino, John-Michael; Nong, Zengxuan; Li, Fuyan; Yin, Hao; Ghonaim, Nour; Milkovich, Stephanie; Balint, Brittany; O'Neil, Caroline; Fraser, Graham M.; Goldman, Daniel; Ellis, Christopher G.; Pickering, J. Geoffrey
Abstract : Rationale: : Angiogenesis occurs after ischemic injury to skeletal muscle, and enhancing this response has been a therapeutic goal. However, to appropriately deliver oxygen, a precisely organized and exquisitely responsive microcirculation must form. Whether these network attributes exist in a regenerated microcirculation is unknown, and methodologies for answering this have been lacking. Objective: : To develop 4-dimensional methodologies for elucidating microarchitecture and function of the reconstructed microcirculation in skeletal muscle. Methods and Results: : We established a model of complete microcirculatory regeneration after ischemia-induced obliteration in the mouse extensor digitorum longus muscle. Dynamic imaging of red blood cells revealed the regeneration of an extensive network of flowing neo-microvessels, which after 14 days structurally resembled that of uninjured muscle. However, the skeletal muscle remained hypoxic. Red blood cell transit analysis revealed slow and stalled flow in the regenerated capillaries and extensive arteriolar-venular shunting. Furthermore, spatial heterogeneity in capillary red cell transit was highly constrained, and red blood cell oxygen saturation was low and inappropriately variable. These abnormalities persisted to 120 days after injury. To determine whether the regenerated microcirculation could regulate flow, the muscle was subjected to local hypoxia using an oxygen-permeable membrane. Hypoxia promptly increased red cell velocity and flux in control capillaries, but in neocapillaries, the response was blunted. Three-dimensional confocal imaging revealed that neoarterioles were aberrantly covered by smooth muscle cells, with increased interprocess spacing and haphazard actin microfilament bundles. Conclusions: : Despite robust neovascularization, the microcirculation formed by regenerative angiogenesis in skeletal muscle is profoundly flawed in both structure and function, with no evidence for normalizing over time. This network-level dysfunction must be recognized and overcome to advance regenerative approaches for ischemic disease. Abstract : Supplemental Digital Content is available in the text.